Synchronous and asynchronous updates of active Ising spins in one dimension - Kumar A.; Pattanayak S.; Singh R.K.; Mishra S. (My University, 2025)
How do update rules affect the dynamical and steady state properties of a flock? In this study, we have explored the active Ising spins (s=±1) in one dimension, where spin updates its orientation according to the Metropolis algorithm (based on the neighbours) via two different update rules. (i) Parallel, and (ii) Random-sequential. We explore the effect of Parallel and Random-sequential updates on the dynamical properties of flocks in one dimension. Due to the inherent asynchronous nature of the Random-sequential update, the directional switching of the flock is increased compared to the Parallel one. The nature of phase transition is affected by the difference in the updating mechanism: discontinuous for Parallel and continuous for Random-sequential updates. © 2024 Elsevier B.V.